Blood on the tide - Robert, Katee (Robert, Katee. Crimson sails series., 2024)
"As a bloodline vampire, Lizzie has never had a problem taking what she wants, and right now what she wants are the family heirlooms that were stolen from her and a portal home. Too bad even that short list is impossible to accomplish on her own-and her allies have bigger things to worry about. When they rescue a selkie from captivity, it's the perfect solution to her problem. Lizzie needs a guide through Threshold and the selkie needs someone to help her get her skin back. Maeve didn't choose to give up her skin-it was stolen from her. Now she's in an uneasy partnership with a dangerous woman who seems more apt to kill than to share a kind word. It's terrifying...and a bit alluring. Even though she knows it will end in heartbreak, Maeve can't help being drawn to Lizzie and her all-too-pleasurable vampire bite. Unfortunately, the danger to Maeve's heart is the least of her worries. The ship Lizzie's chasing belongs to the Cŵn Annwn, and they don't take kindly to people who steal from them. Not even Lizzie's viciousness or Maeve's selkie strength will be enough to save them if the Cŵn Annwn seek retribution..."--